Analysis of the Factors Influencing Teacher Work Motivation at Madrasah Ibtidaiyah Negeri 2 Kerinci - Ahmad Yani (International Journal of Science and Society, 2023)
This study aims to analyze the factors that influence the work motivation of teachers in Madrasah Ibtidaiyah Negeri 2 Kerinci. The research was conducted using a multiple linear regression analysis approach to determine the significance of the factors affecting the work motivation of teachers. The research data were collected through a survey using a questionnaire. The sample consisted of 80 teachers from Madrasah Ibtidaiyah Negeri 2 Kerinci. The results of the study show that the factors of job satisfaction, work environment and compensation have a significant influence on the work motivation of teachers. Meanwhile, the factors of leadership style and workload do not significantly influence the work motivation of teachers. This study provides useful information for school administrators and policy makers in improving the work motivation of teachers.